Analysis of Internal Migration in Poland with Application of the Gravity Model - Pietrzak, Michał Bernard; Wilk, Justyna; Matusik, Stanisław (Acta Universitatis Lodziensis. Folia Oeconomica, 2013)
The subject of this paper is to consider internal migration phenomena in Poland in the years 2008-2011 with application of the gravity model. The period of time covers world financial and economic crisis which hinders economic growth in Poland and impedes internal migration flows. In the investigation 16 Polish voivodships were considered. The values of migration flows (for a permanent residence), related to inter- and intraregional flows constitute a dependent variable. As explanatory variables GDP per capita and registered unemployment rate, for which separate gravity models were specified, including also geographical distance, were selected. Estimation results provide an evaluation of an intensity and direction influence of explanatory variables on migration phenomena. Voivodships about relatively good economic situation are the centres of population inflow (particularly from neighbouring regions) and their net migration is positive. Territorial mobility of population of poor regions is very low.